Influence of shade on genotypic performance of cluster bean (Cyamopsis tetragonoloba, L. Taub.): Shade influence on cluster bean genotypic performance - Dadheech, Rama; Ramavtar Sharma; Hansraj mahla (Annals of Arid Zone, 2023)
Twelve varieties of guar were evaluated in shade and open environments. Analysis of variance for varieties showed non-significant variations for days to 50% flowering and pods per plant for both shade and open environments while nodes per plant, cluster length, pods per cluster and seeds per pod were non-significant in shade only with other traits being significantly variable in both the environments. As expected for a species of dry habitat, shade avoidance mechanism for most of the traits showed increase in the value under shade however, a small reduction in days to flowering and number of branches was recorded. Yield was significantly correlated with nodes per plant, branches per plant and pods per plant under both the open and shaded environment. However, cluster on branches was though positive in both the environments, it was significant only under shade. Path analysis for shade environment indicated maximum direct effect by cluster on branches followed by days to flower initiation, cluster length and nodes per plant. The increase in yield was accompanied by increase in cluster length, pods per cluster, pod length and seeds per pod indicating increased efficiency of plant under 35% reduced radiation and associated heat stress, probably proved beneficial for seed yield.